Preparation method and application of composite hydrogel loaded with multifunctional quercetin carbon dots
By preparing a composite hydrogel loaded with multifunctional quercetin carbon dots, using dynamic borate bonds to release quercetin carbon dots, the problem of difficulty in the existing materials being able to achieve antibacterial and bone-promoting is achieved, and infectious bones are achieved Effective treatment and bone repair of injury.
Patent Information
- Application Number
- CN202411724506.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
AI Technical Summary
Existing bone repair materials are difficult to achieve antibacterial and bone-promoting multifunctional functions at the same time, and cannot effectively treat infectious bone injuries.
By preparing a composite hydrogel loaded with multifunctional quercetin carbon dots, the quercetin carbon dots and methacrylylated polyglutamic acid grafted with 3-aminophenylboric acid form a dynamic borate ester bond, intelligently responding to infection The high reactive oxygen microenvironment at bone injury releases quercetin carbon dots to remove reactive oxygen and kill bacteria while promoting osteogenesis and vascular regeneration.
It has achieved the early removal of reactive oxygen species and rapid killing of bacteria while promoting bone damage repair, with good mechanical support and degradability, suitable for biological tissue engineering, and has very good application prospects.
Smart Images

Figure HDA0005158862160000011 
Figure HDA0005158862160000012 
Figure HDA0005158862160000013
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a bioremediation hydrogel, and in particular to a preparation method and application of a composite hydrogel loaded with multifunctional quercetin carbon dots. Background Art
[0002] Infectious bone injury has always been a difficult problem in orthopedics in clinical practice, and bacterial infection has caused great obstacles to the treatment of bone injury. First, the ROS level in the bone injury microenvironment will increase abnormally. Excessive ROS will promote the differentiation of osteoclasts and induce the apoptosis of osteoblasts, ultimately leading to bone loss. Secondly, since the injury is directly exposed to the external bacterial environment, bacteria can directly adhere to the bone injury and colonize. Among them, Staphylococcus aureus is the main cause of clinical bone injury infection. With the extensive use of antibiotics in clinical practice, bacteria have developed a certain resistance to drugs, and antibiotic treatment methods have gradually become ineffective. Only when the infection is under certain control can bone repair gradually begin. Finally, bone injuries are often accompanied by the rupture of surrounding blood vessels. This not only reduces the supply of nutrition and multiple active factors required for bone regeneration at the bone injury, seriously hinders the self-regeneration process of bones, but also provides a suitable environment for the growth of bacteria. In order to effectively treat infectious bone injuries, it is necessary to take into account many aspects.
[0003] It is difficult for current bone repair materials to achieve multiple functions such as osteogenesis and antibacterial in a single component. Most of these materials are composites with complicated preparation processes. In order to effectively treat infectious bone injuries, many issues need to be taken into account.
[0004] Therefore, developing bioactive materials with both antibacterial and osteogenic properties to treat infected bone lesions will be a therapeutic strategy with important clinical significance. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a composite hydrogel loaded with multifunctional quercetin carbon dots with both antibacterial and osteogenic properties;
[0006] The second object of the present invention is to provide an application of the composite hydrogel loaded with multifunctional quercetin carbon dots obtained by the above method.
[0007] Technical solution: The preparation method of the composite hydrogel loaded with multifunctional quercetin carbon dots of the present invention comprises the following steps:
[0008] (1) preparing quercetin carbon dots by a hydrothermal method;
[0009] (2) mixing and dissolving methacrylated gelatin and a photoinitiator to obtain a GelMA hydrogel;
[0010] (3) mixing the methacryloylated polyglutamic acid grafted with 3-aminophenylboronic acid with the GelMA hydrogel to obtain the PG hydrogel;
[0011] (4) The quercetin carbon dots are mixed with the PG hydrogel and photo-crosslinked under irradiation with a light source to obtain a composite hydrogel loaded with multifunctional quercetin carbon dots.
[0012] Wherein, in step (1), the particle size of the quercetin carbon dots is 3.0-6.5 nm.
[0013] Wherein, in step (1), the temperature of the hydrothermal reaction is 180-200°C and the time is 8-10h.
[0014] Wherein, in step (1), after the hydrothermal reaction is completed, the mixture is filtered, the filtrate is dialyzed with a dialysis bag, and the dialyzed filtrate is freeze-dried to obtain quercetin carbon dots; the molecular retention capacity of the dialysis bag is 500-1000KDa.
[0015] Wherein, in step (2), the concentration of the methacrylated gelatin in the GelMA hydrogel is 5%-10% W / V.
[0016] Wherein, in step (2), the preparation process of the methacrylylated polyglutamic acid grafted with 3-aminophenylboronic acid is as follows:
[0017] After dissolving γ-polyglutamic acid, an activator is added for activation, and then glycidyl methacrylate (GMA for short) is added for light-proof reaction. After purifying the product, methacrylated polyglutamic acid (referred to as m-PGA) is obtained by freeze-drying. The activation time is 1 to 2 hours, and the light-proof reaction time is 18 to 30 hours. The activator is 4-dimethylaminopyridine (DMAP for short). The mass ratio of γ-polyglutamic acid, DMAP, and glycidyl methacrylate is 4:1:0.01.
[0018] After dissolving methacryloyl polyglutamic acid, an activator is added for activation, and then 4-aminophenylboronic acid is added for light-proof reaction. After purifying the product, the product is freeze-dried to obtain methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid (denoted as PBA-m-PGA); wherein the activation time is 2 to 4 hours, and the light-proof reaction time is 10 to 16 hours; the activator is 1-ethyl-(3-dimethylaminopropyl) carbodiimide (abbreviated as EDC) and N-hydroxysuccinimide (abbreviated as NHS); the mass ratio of the methacryloyl polyglutamic acid, EDC, NHS, and 4-aminophenylboronic acid is 1:1.5:2:1.
[0019] Wherein, in step (3), the concentration of methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid in the PG hydrogel is 1%-5% W / V.
[0020] Wherein, in step (4), the concentration of the quercetin carbon dots in the composite hydrogel is 25-100 μg / ml.
[0021] The composite hydrogel loaded with multifunctional quercetin carbon dots prepared by the above method is used in the preparation of materials for treating infectious bone injuries.
[0022] Principle of the invention: In the composite hydrogel of the present invention, quercetin carbon dots and methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid form dynamic borate bonds, so they can intelligently respond to the highly active oxygen microenvironment at the infected bone lesion, release a large number of quercetin carbon dots, thereby removing excessive active oxygen in the microenvironment in the early stage of implantation, and inducing bacterial death and killing bacteria quickly by destroying the normal metabolic activities of bacteria. In addition, the sustained release of quercetin carbon dots not only achieves long-term antibacterial effect, but also improves the osteogenic microenvironment by promoting osteogenesis and promoting vascularization, thereby promoting bone damage repair. The composite hydrogel of the present invention has good application prospects in the field of treating infectious bone injuries.
[0023] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:
[0024] (1) The present invention forms a dynamic borate ester bond between quercetin carbon dots and methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid in the composite hydrogel, which can eliminate excessive ROS in the damaged area, protect cells from ROS damage, and promote cell proliferation. Therefore, it has both antibacterial and osteogenic effects and has a very good application prospect in biological tissue engineering.
[0025] (2) The composite hydrogel loaded with quercetin carbon dots has good mechanical support and degradability, can simulate the extracellular matrix, is conducive to cell adhesion and proliferation, has a simple preparation method, good stability, and good operability; and the composite hydrogel loaded with quercetin carbon dots can respond to the high ROS microenvironment at the site of infectious bone injury and degrade to release quercetin carbon dots;
[0026] (3) The composite hydrogel loaded with quercetin carbon dots has an interconnected macroporous structure and excellent biocompatibility, a short preparation cycle, and can be used to simulate natural tissue structures;
[0027] (4) Quercetin carbon dots have efficient bactericidal properties, good osteogenesis ability and the ability to promote angiogenesis. The preparation method is simple. The release of quercetin carbon dots can effectively improve the repair of tissue damage caused by bacterial invasion in a tissue damage environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 TEM image of quercetin carbon dots in Example 1;
[0029] Figure 2This is the Fourier infrared spectrum image of the quercetin carbon dots in Example 1;
[0030] Figure 3 This is the SEM image of the composite hydrogel loaded with quercetin carbon dots in Example 1;
[0031] Figure 4 This is a Fourier transform infrared spectrum image of the composite hydrogel loaded with quercetin carbon dots in Example 1;
[0032] Figure 5 The antibacterial pictures of quercetin carbon dots prepared at different temperatures in Example 1, Comparative Example 1 and Comparative Example 2;
[0033] Figure 6 The CCK-8 detection diagram of the composite hydrogel loaded with different concentrations of quercetin carbon dots in Examples 1-3 and Comparative Example 3;
[0034] Figure 7 The antibacterial flat plate coating experiment diagram of the composite hydrogel loaded with different concentrations of quercetin carbon dots in Examples 1-3 and Comparative Example 3;
[0035] Figure 8 It is a western blot experimental diagram of the composite hydrogel loaded with different concentrations of quercetin carbon dots in Examples 1-3 and Comparative Example 3. DETAILED DESCRIPTION
[0036] The present invention is described in further detail below.
[0037] Example 1
[0038] A method for preparing a composite hydrogel loaded with multifunctional quercetin carbon dots comprises the following steps:
[0039] (1) 0.005 g of quercetin and 10 mL of deionized water were fully mixed, then sealed in a steel autoclave with a polytetrafluoroethylene liner, and reacted in a muffle furnace at 180°C for 8 hours; after the reaction was completed, the solution was cooled to room temperature and filtered with a needle filter with a pore size of 0.22 mm; the reaction filtrate was collected and dialyzed with a dialysis bag with a molecular cutoff of 1000 KDa for 36 hours, and the dialysate was replaced every 6 hours. The solution in the dialysis bag was then collected and placed in a -80°C refrigerator for frozen storage, and finally freeze-dried to obtain gray-black solid quercetin carbon dots.
[0040] (2) Preparation of methacryloyl polyglutamic acid (m-PGA): Use a beaker to dissolve 5 g of γ-polyglutamic acid in 50 mL of deionized water under stirring at room temperature. After dissolution, add 125 mg of 4-dimethylpyridine (DMAP). After activation for 1 hour, add 1.25 ml of glycidyl methacrylate (GMA) and react in the dark for 24 hours. Then, dialyze for 3 days to purify the product and freeze-dry to obtain m-PGA.
[0041] Preparation of methacryloyl polyglutamic acid grafted with phenylboronic acid (PBA-m-PGA): Dissolve 100 mg of m-PGA in 60 mL of water under stirring at room temperature in a beaker, add 150 mg of EDC and 200 mg of NHS after m-PGA is dissolved, activate at room temperature for 3 hours, add 100 mg of 4-aminophenylboronic acid (PBA), react for 12 hours, and protect from light during the reaction. After the reaction is completed, dialyze for 3 days to purify the product, and freeze-dry to obtain PBA-m-PGA.
[0042] (3) Take 1 g of GelMA and 0.05 g of photoinitiator LAP, add them into 20 ml of deionized water, and fully dissolve them to obtain GelMA hydrogel; wherein the concentration of GelMA in the GelMA hydrogel is 5% W / V.
[0043] (4) PBA-m-PGA was mixed with GelMA hydrogel to prepare PG hydrogel; wherein the concentration of PBA-m-PGA in PG hydrogel was 5% W / V.
[0044] (5) The quercetin carbon dots and the PG hydrogel were fully mixed, and irradiated with a blue light source with a wavelength of 405 nm for 1 minute to prepare a quercetin carbon dot-loaded composite hydrogel; wherein the concentration of the quercetin carbon dots in the composite hydrogel was 100 μg / ml.
[0045] like Figure 1 As shown, the TEM image of the quercetin carbon dots prepared in step (1) of Example 1 of the present invention shows that the quercetin carbon dots are spherical particles with uniform particle size, and the particle size is about 3.0-6.5 nm.
[0046] like Figure 2 As shown, Q represents quercetin and QCD represents quercetin carbon dots; from the Fourier infrared spectrum image of quercetin carbon dots, it can be seen that the prepared quercetin carbon dots retain some important functional groups, including -OH, C=C and COC.
[0047] like Figure 3 As shown, from the SEM image of the composite hydrogel loaded with quercetin carbon dots prepared in step (5), it can be seen that the composite hydrogel has an interconnected macroporous structure, which is conducive to the adhesion and growth of cells.
[0048] like Figure 4 As shown, the Fourier transform infrared spectrum image of the composite hydrogel loaded with quercetin carbon dots prepared in step (5) can confirm the successful grafting of phenylboronic acid.
[0049] Example 2
[0050] On the basis of Example 1, the difference from Example 1 is that in step (5), the concentration of quercetin carbon dots in the composite hydrogel is 25 μg / ml.
[0051] Example 3
[0052] On the basis of Example 1, the difference from Example 1 is that in step (5), the concentration of quercetin carbon dots in the composite hydrogel is 50 μg / ml.
[0053] Example 4
[0054] On the basis of Example 1, the difference from Example 1 is that in step (1), in the step of collecting the reaction filtrate during the preparation of quercetin carbon dots, a dialysis bag with a molecular cutoff of 500 KDa is used for dialysis.
[0055] Example 5
[0056] On the basis of Example 1, the difference from Example 1 is that in step (1), in the step of collecting the reaction filtrate during the preparation of quercetin carbon dots, a dialysis bag with a molecular cutoff of 2000 KDa is used for dialysis.
[0057] Comparative Example 1
[0058] On the basis of Example 1, the difference from Example 1 is that in step (1), the hydrothermal reaction temperature for preparing quercetin carbon dots is set to 200°C.
[0059] Comparative Example 2
[0060] On the basis of Example 1, the difference from Example 1 is that in step (1), the hydrothermal reaction temperature for preparing quercetin carbon dots is set to 220°C.
[0061] Comparative Example 3
[0062] On the basis of Example 1, the difference from Example 1 is that in step (5), the concentration of quercetin carbon dots in the composite hydrogel is 200 μg / ml.
[0063] 1. The antibacterial properties of quercetin carbon dots obtained at different hydrothermal reaction temperatures in Example 1 and Comparative Examples 1 and 2 were tested:
[0064] like Figure 5As shown in the figure, the quercetin carbon dots prepared at three different temperatures of 180℃, 200℃ and 220℃ have the least residual bacteria after treatment, so the quercetin carbon dots obtained under this hydrothermal temperature condition have the best antibacterial effect. The quercetin carbon dots obtained under the reaction conditions of 200℃ and 220℃ have lower quercetin carbon dot content in the reactants than those obtained under the reaction conditions of 180℃, that is, lower purity, while the quercetin carbon dots obtained under the reaction conditions of 180℃ have higher purity.
[0065] 2. Comparison of the biocompatibility, antibacterial ability and osteogenic ability of the composite hydrogels loaded with different concentrations of quercetin carbon dots in Examples 1-3 and Comparative Example 3:
[0066] Different hydrogels were co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 1, 3, and 5 days, and the proliferation of cells on the composite hydrogels was detected by CCK-8 method. Figure 6 As shown, Figure 6 The horizontal axis is time, and the vertical axis is absorbance at a wavelength of 450 nanometers; Figure 6 Ctrl is the control group, PG is the composite hydrogel formed by GelMA hydrogel and PBA-m-PGA, CPG is the composite hydrogel formed after adding quercetin carbon dots, and the lower right corner of CPG represents the concentration of quercetin carbon dots added; the asterisk on the horizontal line indicates that there is a statistical difference, and ns indicates that there is no statistical difference. Figure 6 It can be seen that the composite hydrogels with quercetin carbon dot concentrations of 25, 50 and 100 μg / ml can promote cell proliferation on the 1st, 3rd and 5th days, while the composite hydrogel with quercetin carbon dot concentration of 200 μg / ml in Comparative Example 1 showed obvious cytotoxicity.
[0067] like Figure 7 As shown, 20 μL of Staphylococcus aureus suspension with a concentration of 106 CFU / mL was added to the surface of each group of hydrogels, and the antibacterial ability of different hydrogels was detected after co-culture for 24 hours. It can be seen that the composite hydrogel with a quercetin carbon dot concentration of 100 μg / ml in Example 1 has the strongest antibacterial effect.
[0068] Different hydrogels were co-cultured with bone marrow mesenchymal stem cells (BMSCs) for 7 and 14 days, and the expression of osteogenic proteins in the early stage (7 days: RUNX2 and ALP) and late stage (21 days: COL1 and OCN) were detected by immunoblotting. Figure 8 As shown, Figure 8 Left vertical axis: osteopontin (OPN); Runt-related transcription factor 2 (RUNX2); glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Figure 8The vertical axis of the middle right figure: type I collagen (COL1); osteocalcin (OCN); glyceraldehyde-3-phosphate dehydrogenase (GAPDH), Figure 8 The Ctrl in the horizontal axis of the left and right figures is the control group, and Induced represents the positive induced group. Figure 8 It can be seen that for the CPG100 group, the expression of early osteogenesis-related proteins such as OPN and RUNX2 is the highest among the five groups. Similarly, late osteogenesis-related proteins such as COL-1 and OCN also have the highest expression levels. Therefore, the quercetin carbon dot concentration of 100 μg / ml has the strongest osteogenic effect. In addition, for the CPG50 group, the expression of osteogenesis-related proteins is also more obvious.
Claims
1. A method for preparing a composite hydrogel loaded with multifunctional quercetin carbon dots, characterized in that: The following steps are involved: (1) preparing quercetin carbon dots by a hydrothermal method; (2) mixing and dissolving methacrylated gelatin and a photoinitiator to obtain a GelMA hydrogel; (3) mixing the methacryloylated polyglutamic acid grafted with 3-aminophenylboronic acid with the GelMA hydrogel to obtain the PG hydrogel; (4) The quercetin carbon dots are mixed with the PG hydrogel and photo-crosslinked under irradiation with a light source to obtain a composite hydrogel loaded with multifunctional quercetin carbon dots.
2. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (4), the concentration of the quercetin carbon dots in the composite hydrogel is 25-100 μg / ml.
3. The method for preparing the composite hydrogel loaded with multifunctional melatonin carbon dots according to claim 1, characterized in that: In step (1), the particle size of the quercetin carbon dots is 3.0-6.5 nm.
4. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 180-200° C. and the time is 8-10 h.
5. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (1), after the hydrothermal reaction is completed, the mixture is filtered, the filtrate is dialyzed using a dialysis bag, and the dialyzed filtrate is freeze-dried to obtain quercetin carbon dots.
6. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 5, characterized in that: The molecular cut-off of the dialysis bag is 500-1000 KDa.
7. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (2), the concentration of the methacrylated gelatin in the GelMA hydrogel is 5%-10% W / V.
8. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (3), the concentration of methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid in the PG hydrogel is 1%-5% W / V.
9. The method for preparing the composite hydrogel loaded with multifunctional quercetin carbon dots according to claim 1, characterized in that: In step (2), the preparation process of the methacrylylated polyglutamic acid grafted with 3-aminophenylboronic acid is as follows: After dissolving γ-polyglutamic acid, an activator is added for activation, and then glycidyl methacrylate is added for light-protected reaction, and the product is purified and freeze-dried to obtain methacrylylated polyglutamic acid; After dissolving the methacryloyl polyglutamic acid, an activator is added for activation, and then 4-aminophenylboronic acid is added for light-protected reaction. After purifying the product, the methacryloyl polyglutamic acid grafted with 3-aminophenylboronic acid is obtained by freeze-drying.
10. Use of a composite hydrogel loaded with multifunctional quercetin carbon dots prepared by the method according to claim 1 in preparing materials for treating infectious bone injuries.